Personal finance - Keown, Arthur J. (Uttar Pradesh, India Pearson India education services Pvt. Ltd., 2020)
Turning Money into Wealth empowers students to successfully make and carry out a plan for their financial future. By introducing the 10 fundamental principles of personal finance in a way that leaves a lasting impression, this text offers students lifelong tools that will help them effectively cope with an ever-changing financial environment. The 8th Edition reflects recent changes in the world of personal finance, including new tax laws, the economic downturn, weakness in the labor markets, the explosion of student loans, and the rise of credit card debt.